Industry experiences of environmentally conscious design integration : an exploratory study - McAloone, Timothy Charles (Cranfield University, 1998)
This research has explored environmentally conscious design in the electrical/electronics industry sector. In this new and rapidly evolving field, existing research has not yet sought to understand the causes of success and the problems experienced when companies have integrated environmental considerations into the design process. In the context of advanced practitioners of environmentally conscious design in the Western European and North American electrical/electronics industry sector, it is shown that: - the timing of environmental decisions in the design process is key to environmentally conscious design; - the environmental profile of a product is affected the most in the very early stages of the design process, particularly in the pre-specification stage, where tools for environmentally conscious design decision-making are lacking; - an enthusiastic approach, driven by an environmental champion, is key to environmentally conscious design; - top management commitment is important for successful environmentally conscious design; - there is a common sequence of events that many companies go through when integrating environmentally conscious design into their product development processes. This starts with motivation, leading to widening communication and information flows and finally to whole-life thinking. These findings emerged from one in-depth study and a transatlantic industry survey, interviewing twenty four practitioners. A framework of factors affecting environmentally conscious design was derived from this research and a model of environmentally conscious design integration developed which describes the industry's experience of integrating environmental considerations into the design processes.